OC15 Paediatric mild traumatic brain injury is associated with systemic inflammasome activation and pubertal scoring. (June 2019) - Ryan, Emer; Kelly, Lynne; Duff, Eimear; Bolger, Turlough; Molloy, Eleanor
Abstract : Background: Mild Traumatic Brain Injury (mTBI) is a common childhood occurrence with a more severe phenotype in adolescence. Systemic inflammation has been demonstrated to be integral to the pathogenesis of ongoing symptoms. The inflammasome is a component of innate immunity that is involved in regulating and inducing inflammation in response to cell damage and may have a modifiable role in mTBI. Objective: We demonstrated inflammasome pathway activation in response to mTBI. We hypothesized that pubertal development modulates inflammasome activation. We correlated pubertal scores with inflammasome gene transcription. Methods: Children were recruited to the study following presentation to the emergency department with symptomatic head injuries (GCS 14/15; n=21) and compared to age-matched Controls (n=10). Pubertal developmental self-rating scales (PDS) with 5 rating questions were administered with a maximum score of 20. mRNA was extracted from whole blood and the Inflammasome components [Interleukin (IL)- 1beta and NLR Family Pyrin Domain Containing 3 (NLRP3)] in mTBI and controls were profiled with RT-PCR analysis on the ABI 7900. Results: The mean age of children recruited was 12.0(±3.9) years with 18 males. Both NLRP3 and IL-1β were significantly raised in the mTBI group versus controls (p<0.0001). IL-1β was significantly downregulated at 2 weeks post TBI (p<0.0001). There was a significant correlation between pubertal score and IL-1β in mTBI (p=0.04). Conclusion: Inflammasome activation via the NLRP3 pathway is important in paediatric mTBI. IL1beta activation was more prominent in children at more advanced stages of puberty. The interplay of pubertal maturity and the innate immune system may explain the greater burden of symptoms in patients during adolescence.